Ecotoxicological assessment of hospital wastewater: analysis of regression models - Gómez-Herrera, Santiago [UNESP]; Santacruz-Salas, Angie P. [UNESP]; Alves Macedo, João Carlos [UNESP]; Beltrán, Javier A.; Paz, Juan D.; Morales, Diana C.; Rosero, James A.; Rosa, André H. [UNESP] (Taylor & Francis, 2022)
This study assessed different regression models to estimate the concentration that inhibits 50% of Allium cepa root growth after exposure to different concentrations (5 to 100%v/v) of hospital wastewater for 72 h. In addition, the mitotic index was also calculated. The results indicate alterations in the normal development of A. cepa owing to the possible presence of toxic substances, identifying a maximum root inhibition of 61.01% and a minimum mitotic index of 2.15%. The Gompertz model was better than other models for its adequate adjustment and low error with a half maximal inhibitory concentration of 57.5% (moderately toxic waters) and a difference of 23% with traditional models such as Probit (80%) or Log-Logistic (80%). Toxicity tests with bioluminescent bacteria (Vibrio fischeri) confirmed the results obtained from A. cepa bioassays.
Keywords: Allium cepa; gompertz; hospital wastewater; IC50